Early retirement of employees in demanding jobs: Evidence from a German pension reform - Johannes Geyer; Svenja Lorenz; Thomas Zwick; Mona Bruns (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Early retirement options are usually targeted at employees at risk of not reaching their regular retirement age in employment. An important at-risk group comprises employees who have worked in demanding jobs for many years. This group may be particularly negatively affected by the abolition of early retirement options. To measure differences in labor market reactions of employees in low- and high-demand jobs, we exploit the quasi-natural experiment of a cohort-specific pension reform that increased the early retirement age for women from 60 to 63 years. Based on a large administrative dataset, we use a regression-discontinuity approach to estimate the labor market reactions. Surprisingly, we find the same relative employment increase of about 25% for treated women who were exposed to low and to high job demand. For older women in demanding jobs, we do not find substitution effects into unemployment, partial retirement, disability pension, or inactivity. Eligibility for the pension for women required high labor market attachment; thus, we argue that this eligibility rule induced the positive selection of healthy workers into early retirement. We propose alternative policies that protect workers exposed to high job demand better against the negative consequences of being unable to reach their statutory retirement age in employment.
Keywords: J14; J18; J22; J26; H31; 330; pension reform; job demand; early retirement; quasi-experimental variation